Defining Inclusionary Education: A Review of Recent Literature - Melissa Garrett (Canadian Society for Studies in Education, 2022)
The purpose of this article is to explore the various constructs and perspectives surrounding the integration and application of the inclusive model of education on a global scale. The article begins by exploring the most common definitions of "inclusion" within the context of education and learners within current literature. It then continues its exploration in a discussion of the focus several education systems have placed on support services to address student areas of challenge. The article concludes with a call to action for the continuation of progress in the realm of inclusionary education through the promotion of student strengths. This article imposes critical considerations for the identification, amplification, and application of these strengths in all areas of learning within the inclusionary model of education.